Implementasi Sistem Enterprise Resource Planning pada Toko Gemilang 888 - Salim, Alissa; Susilo, Joko (Jurnal Informatika dan Bisnis, 2025)
In today's digital era, the use of ERP (Enterprise Resource Planning) systems has become a strategic solution for businesses to manage operations more efficiently and in an integrated manner. Toko Gemilang 888, a retail business, faces challenges in managing sales data, inventory, and financial reports, which are still handled manually. This study aims to implement a web-based ERP (Enterprise Resource Planning) system to improve operational efficiency, minimize errors, and accelerate business processes at Toko Gemilang 888. The methods used include system requirements analysis, ERP system model design, and implementation testing to ensure the system operates according to business needs. The design of the ERP system at Toko Gemilang 888 aims to enhance operational efficiency by automating inventory tracking, invoice generation, and report preparation through a web-based architecture. The system includes input processes by users via Client PCs, data processing on the Main ERP Server, and output that is displayed back to the users. To support optimal performance, the system requires hardware with a capable processor, sufficient RAM capacity, and high-speed storage. Meanwhile, the software used includes the latest operating system, a PostgreSQL database, and a Flask-based web server. The implementation of the ERP system at Toko Gemilang 888 has successfully improved operational efficiency by automating administrative processes, reducing transaction recording errors, and optimizing inventory management and sales trend analysis. However, the system still has limitations, such as the absence of a transaction deletion feature, which can be addressed by alternatives such as a transaction cancellation feature, stricter data validation, and an audit trail module to maintain transparency.